Sustainable Pavements and Road Materials Proceedings of the 7th SIIV Arena, Naples, Italy 9th September 2022 - Russo, Francesca; Biancardo, Salvatore Antonio; Veropalumbo, Rosa; Abbondati, Francesco (Miscellaneous, 2022)
The SIIV Arena is a space for discussion in which PhD students and young scholars from various universities illustrate their research on topics of specific interest for the Scientific Disciplinary Sector ICAR/04 "Roads, Railways and Airports". This volume collects the proceedings of the 7th SIIV Arena, held in Naples on 9 September 2022, and held as part of the XVIII International SIIV Summer School: "Sustainable Pavements and Road Materials". The use of construction and maintenance technologies based on principles of sustainability, resilience and circular economy, are a reference, in synergy with the use of secondary raw materials, for achieving adequate mechanical performance for the road structure, with a reduced environmental impact. and costs. The growth gradient recorded in the field of civil infrastructures has defined an incessant use of natural resources with consequent negative effects in terms of environmental sustainability. The reuse of waste in mix design processes and the use of in situ processing systems and/or "low energy" technologies (i.e., cold and/or warm asphalt mixtures) fully meet the objectives underlying the principles of the circular economy. This volume aims to collect the most innovative research in the sector presented in the context of the 7th SIIV Arena by analyzing aspects relating to the design, construction and maintenance of the pavement and road infrastructure as a whole.